Nuclear PKM2 contributes to gefitinib resistance via upregulation of STAT3 activation in colorectal cancer - Li, Qiong; Zhang, Daoxiang; Chen, Xiaoying; He, Lei; Li, Tianming; Xu, Xiaoping; Li, Min (Scientific reports, 2015)
Gefitinib (Iressa, ZD-1839), a small molecule tyrosine kinase inhibitor (TKI) of the epidermal growth factor receptor (EGFR) pathway, is currently under investigation in clinical trials for the treatment of colorectal cancer (CRC). However, as known, some patients develop resistance to TKIs and the mechanisms mediating intrinsic resistance to EGFR-TKIs in CRC have not been fully characterized. Resistance to EGFR inhibitors reportedly involves activation of signal transducer and activator of transcription 3 (STAT3) in glioma and lung cancer. Here, we demonstrated that the nuclear pyruvate kinase isoform M2 (PKM2) levels were positively correlated with gefitinib resistance in CRC cells. The overexpression of nuclear PKM2 in HT29 cells decreased the effect of gefitinib therapy, whereas PKM2 knockdown increased gefitinib efficacy. Furthermore, the activation of STAT3 by nuclear PKM2 was associated with gefitinib resistance. Inhibition of STAT3 by Stattic, a STAT3-specific inhibitor, or STAT3-specific siRNA sensitized resistant cells to gefitinib. These results suggest that nuclear PKM2 modulates the sensitivity of CRC cells to gefitinib and indicate that small molecule pharmacological disruption of nuclear PKM2 association with STAT3 is a potential avenue for overcoming EGFR-TKI resistance in CRC patients.